Study of laryngeal lesions undergoing microlaryngeal surgery in a tertiary health centre - K. S., Gangadhara; Vadva, Chaitanya; S., Sridhara (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Patients with laryngeal lesions were evaluated for age and sex ratio, analysis of clinical features, videolaryngoscopic findings and histopathological features. Assessment of therapeutic role of microlaryngeal surgery (MLS) by telescopic method and also prognosis after surgery and voice therapy were evaluated. Methods: A prospective institutional based study. A total of 18 patients with vocal cord lesions the chief complaint being hoarseness of voice were subjected to surgery in a tertiary health centre. After thorough evaluation patients underwent MLS by telescopic method. Results: In our study 6 patients stand out to be benign lesions and 12 patients stand out to be pre malignant and malignant lesions. Improvement in voice after surgery was reported in all patients. No recurrence was reported after 6-8 months of follow-up. Conclusions: MLS is a good tool as it is precise and cost effective. MLS by telescopic method is a good therapeutic tool in both benign and malignant vocal cord lesions.